PENGARUH LOCUS OF CONTROL, GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI PADA KINERJA AUDITOR KANTOR AKUNTAN PUBLIK - Putri Sanjiwani, Desak Made; Suparta Wisadha, I Gede (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
The accounting profession has an important role in the provision of reliable financial information for the government, investors, creditors, shareholders, employees, debtors, also for the community and other parties concerned. The performance of auditors is the ability of an auditor to produce findings or results of the examination of inspection activities for the management and financial responsibilities are carried out in an inspection team. Factors affecting the performance of the auditor is locus of control, leadership style and organizational commitment.The purpose of this study was to determine the effect of locus of control, leadership style and organizational commitment on the performance of auditors of public accounting firms in the province of Bali. Research tool used was a data analysis technique multiple linear regression, test F-test and t test. The location study performed at the Public Accounting Firm (KAP), which is in the province of Bali. Based on the results of analysis show that the locus of control, leadership style and organizational commitment have positive influence on the performance of auditors of public accounting firms in the province of Bali.
Keywords: locus of control, leadership styles, organizational commitment, performance auditor